2011
DOI: 10.1007/s10144-011-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of excessive deer browsing through understory vegetation on stream insect assemblages

Abstract: Over the past decade, the abundance of sika deer has rapidly increased around Japan. Previous studies have showed overabundance of deer causes drastic reduction of forest understory vegetation, leading excessive soil erosion. However, no study has investigated the effects of excessive deer browsing on aquatic insect assemblages via sediment runoff. These effects are important to understand whether the terrestrial alteration by deer influences aquatic ecosystems. In a primary deciduous forest catchment in Ashiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…This pattern contrasts with the rapid response to forest degradation seen in headwater streams in the Ashiu Research Forest. Sakai et al (2012Sakai et al ( , 2013 reported that an increase in fine sediments in a streambed was clearly observable in first-order streams 2 or 3 years after the forest degradation event in 2006. This difference may be due to the time lag of downstream sediment transportation, which depends on the distance between upstream and downstream sites and seasonal and annual variations in water discharge, including flood disturbance events (Church, 2002;Hamilton, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern contrasts with the rapid response to forest degradation seen in headwater streams in the Ashiu Research Forest. Sakai et al (2012Sakai et al ( , 2013 reported that an increase in fine sediments in a streambed was clearly observable in first-order streams 2 or 3 years after the forest degradation event in 2006. This difference may be due to the time lag of downstream sediment transportation, which depends on the distance between upstream and downstream sites and seasonal and annual variations in water discharge, including flood disturbance events (Church, 2002;Hamilton, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Deer overabundance not only affects terrestrial ecosystems but can also spread to aquatic ecosystems. These increased sediment inputs affect the community structure of macroinvertebrate assemblages via changes in the physical characteristics of stream habitats (Sakai et al, 2012. These increased sediment inputs affect the community structure of macroinvertebrate assemblages via changes in the physical characteristics of stream habitats (Sakai et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive deer browsing has caused drastic decreases in the abundance and diversity of understory plants since the late 1990s (Kato and Okuyama 2004;Tanaka et al 2008). Soil erosion via denudation by deer has increased sediment runoff and subsequent sandy sedimentation of streambeds in deciduous forests (Sakai et al 2012).…”
Section: Study Sitementioning
confidence: 99%
“…Through selective feeding, deer directly affect forest communities by altering species composition and vegetation structure (C么t茅 et al 2004;Takatsuki 2009;Habeck and Schultz 2016). These direct effects have the potential to indirectly alter the abundance of co-occurring animal species (Rooney 2001;Rooney and Waller 2003;Sakai et al 2012). For example, through resource competition, deer can negatively affect the abundance of small granivorous mammals.…”
Section: Introductionmentioning
confidence: 99%